Promotion of Community Resilience through Citizen Science Approaches - Daniel, Ana Dias (Contesti. Città, territori, progetti, 2026)
The promotion of community resilience is a complex and understudied phenomenon. This article aims to contribute to this literature gap by assessing the role of citizen science (CS) approaches in the development of community resilience, since CS is considered a promising approach for generating new knowledge through fostering the participation of citizens (non-professional scientists) in research activities. The results show that CS approaches are relevant for developing resilience abilities through i) the collection of new data from new sources or remote places where data is scarce, allowing for a better characterization of potential hazards, and the identification of community needs, perceptions and behaviours; ii) enhancing community awareness and knowledge about hazard protection; iii) increase human and social capital through specific training initiatives; and iv) promote the cooperation between community (citizens), academia (professional scientists) and government (policymakers), which is relevant for the development of public policies shaped to local context, and aligned with community’s needs and expectations.